1997
DOI: 10.1086/516461
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Retinal Toxicity and Efficacy of Anti‐Cytomegalovirus and Anti‐Herpes Simplex Virus Antiviral Phosphorothioate Oligonucleotides ISIS 2922 and ISIS 4015

Abstract: Retinal toxicity of ISIS 2922 and ISIS 4015, phosphorothioate oligonucleotides complementary to human cytomegalovirus (CMV) and herpes simplex virus (HSV) RNA, were evaluated. The intravitreal concentration of ISIS 2922 found not to cause permanent toxic changes in the rabbit retina was 10 microM and in the pig retina, 5 microM. The 3 microM concentration was associated with a transient inflammatory response, and 1 microM caused no retinal toxicity or inflammation. ISIS 4015 showed very mild toxicity with no p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

1998
1998
2005
2005

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 25 publications
(7 reference statements)
0
16
1
Order By: Relevance
“…These adverse effects were particularly evident with the highest dose (50 l, 0.75 nmol/ l), indicating that the volume and concentration of DS135 needs to be further adjusted. Although the cellular infiltration could be minimized by IV use of certain amounts of antiinflammatory drugs (Danis et al, 2000;Flores-Aguilar et al, 1997;Shen et al, 2000), our results may also imply that the undesired side effects of DS135 are associated with the biochemical structure of PS-oligo (Black et al, 1994;Dvorchik and Marquis, 2000). It has been reported that chimeric oligonucleotides consisting of a mixed phosphodiester-phosphorothioate backbone and having 2-methoxyrobonucleotides modification, dramatically eliminated the side effects of PS-oligos but retained the effective potency in the central nerve system (Ho et al, 1998).…”
Section: Ps-oligo In the Retina Of Rhesus Monkeymentioning
confidence: 83%
See 1 more Smart Citation
“…These adverse effects were particularly evident with the highest dose (50 l, 0.75 nmol/ l), indicating that the volume and concentration of DS135 needs to be further adjusted. Although the cellular infiltration could be minimized by IV use of certain amounts of antiinflammatory drugs (Danis et al, 2000;Flores-Aguilar et al, 1997;Shen et al, 2000), our results may also imply that the undesired side effects of DS135 are associated with the biochemical structure of PS-oligo (Black et al, 1994;Dvorchik and Marquis, 2000). It has been reported that chimeric oligonucleotides consisting of a mixed phosphodiester-phosphorothioate backbone and having 2-methoxyrobonucleotides modification, dramatically eliminated the side effects of PS-oligos but retained the effective potency in the central nerve system (Ho et al, 1998).…”
Section: Ps-oligo In the Retina Of Rhesus Monkeymentioning
confidence: 83%
“…To date, most studies have involved IV administration of PS-oligo into the eye (Dvorchik and Marquis, 2000;Flores-Aguilar et al, 1997;Hangai et al, 1998;Leeds et al, 1997Leeds et al, , 1998Ogata et al, 1999;Rakoczy et al, 1996;Robinson et al, 1996;Shen et al, 1999;Stone and Jaffe, 2000). It has been reported that high doses of PS-oligos after IV injection induce cataract, severe inflammatory response, increased intraocular pressure, maculopathy, and permanent retinal damage (Detrick, 2001;Dvorchik and Marquis, 2000;Flores-Aguilar et al, 1997;Stone and Jaffe, 2000). These adverse effects could be serious limitations to the potential use of high doses of PS-oligos by IV injection in humans.…”
Section: Shen Et Almentioning
confidence: 99%
“…The extracellular particle is negatively stained with uranyl-acetate (4% aqueous solution). The bar represents 100 nm immediate early transcription unit of CMV and inhibits protein synthesis [30][31][32][33]. It is being studied as an intravitreal treatment for CMV retinitis, but it has severe side effects, like vitritis and retinal pigment epithelial stippling.…”
Section: Introductionmentioning
confidence: 99%
“…The only antisense oligonucleotide that has been formally approved as an antiviral drug is ISIS 2922 (formiversen). This molecule shows protection against CMV retinitis in AIDS patients when injected intravitreally (64,160). Although antisense oligonucleotides are designed to act in a very selective way by sequence-dependent binding, side effects are not uncommon, since interaction with DNA (triplex formation) and proteins (through simple charge interactions or even sequence-dependent binding) may also occur (7,23).…”
Section: Antisense Oligonucleotide Therapymentioning
confidence: 99%